A clustering algorithm based on jet algorithms for cross-talk events in neutron detector arrays - Dogangun, O.; Özok, F.; Dündar, U.; Erduran, Mustafa Nizamettin; Erduran, Mustafa Nizamettin (IOP Publishing Ltd., 2022)
A clustering algorithm based on the jet (cascade of particles descendant from a single particle due to hadronization) algorithms used in High Energy Physics is presented for identification of neutron cross-talk events in neutron detector arrays with one layer by defining a temporal distance function, instead of transverse energy. Detector simulations on an array of neutron detectors show a significant improvement when compared with neighbor rejection technique and the method of gating with time-of-flight difference. © 2022 IOP Publishing Ltd and Sissa Medialab.
Keywords: Neutron detectors (cold, thermal, fast neutrons); Particle identification methods; Pattern recognition; Cluster finding; Calibration and fitting methods; Simulation methods and programs